Immune Infiltration Characteristics and a Gene Prognostic Signature Associated With the Immune Infiltration in Head and Neck Squamous Cell Carcinoma - Zhu, Chunmei; Wu, Qiuji; Yang, Ningning; Zheng, Zhewen; Zhou, Fuxiang; Zhou, Yunfeng (Frontiers in Genetics, 2022)
Background: Immunotherapy has become new standard of care for recurrent and metastatic head and neck squamous cell carcinoma (HNSCC), and PD-L1 is a widely used biomarker for immunotherapeutic response. However, PD-L1 expression in most cancer patients is low, and alternative biomarkers used to screen the population benefiting from immunotherapy are still being explored. Tumor microenvironment (TME), especially tumor immune infiltrating cells, regulates the body's immunity and affect the tumor growth, and is expected to be a promising biomarker for immunotherapy. Purpose: This article mainly discussed how the immune infiltrating cell patterns impacted on immunity, thereby affecting HNSCC patients' prognosis. Method: Immune infiltrating cell profile was generated by the CIBERSORT algorithm based on the transcriptomic data of HNSCC. Consensus clustering was used to divide groups with different immune cell infiltration patterns. Differentially expressed genes (DEGs) obtained from the high and low immune cell infiltration (ICI) groups were subjected to Kaplan-Meier and univariate Cox analysis. Significant prognosis-related DEGs were involved in the construction of prognostic signature using multivariate Cox analysis. Results: In our study, 408 DEGs were obtained from high- and low-ICI groups and 59 of them were significantly associated with overall survival (OS). Stepwise multivariate Cox analysis developed a 16-gene prognostic signature, which could distinguish favorable and poor prognosis of HNSCC patients. ROC curve and nomogram verified the sensitivity and accuracy of the prognostic signature. AUC values for 1 year, 2 years, 3 years were 0.712, 0.703, 0.700. TCGA-HNSCC cohort, GSE65858 cohort and an independent GSE41613 cohort proved a similar prognostic significance. Notably, the prognostic signature distinguished the expression of promising immune inhibitory receptors (IRs) well and could predict the response to immunotherapy. Conclusion: We established a tumor immune cell infiltration (TICI)-based 16-gene signature which could distinguish patients with different prognosis and help predict the response to immunotherapy.